Aksiologis dalam Pendidikan Indonesia (Tinjauan Pasal 1 Ayat 1 UU No. 20/2003 Tentang Sistem Pendidikan Nasional) - Zakki, Ahmad; Jamaris; Solfema; Husna, Assaidatul; Adha, Idyana; Al-Mitsaq, Hafiz; Haq, Olim Zul Ilmil; Nasution, Salsabila (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The study of this article focuses on the value produced by education in Indonesia contained in Article 1 Paragraph 1 of Law No. 20/2003 concerning the National Education System, which explains that education is to create a learning atmosphere and learning process, so that students can actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills with the aim of having value for themselves, society, nation and country. This is realized consciously and planned by the teachers. Education is successful if the values in developing the potential for religious spiritual strength, self-control, personality, intelligence, noble character, and skills can be implemented properly by the teacher and this potential develops in each student.